DETERMINAN MANAJEMEN PAJAK DENGAN INDIKATOR TARIF PAJAK EFEKTIF PADA PERUSAHAAN MANUFAKTUR - Murtia ningsih; Brilliant Arif Wijaya (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2021)
This research aims to find out and analyze the determinant on tax management with indicators of effective tax rates on manufacturing companies listed on the IDX. The research uses secondary data in the form of financial statements from the IDX www.idx.co.id. The population in this study was a manufacturing company registered in the IDX period 2018-2019. The sampling technique used is purposive sampling, and obtained as many as 84 companies or 168 samples. Research approach using quantitative approach. The results showed that profitability affects tax management, while the level of corporate debt and intensity of fixed assets have no effect on tax management. Keywords: Profitability, Corporate Debt Level, Fixed Asset Intensity, Tax Management, Effective Tax Rate